The role of fertilizers in transforming of agriculture in Asia: A case study of Indian fertilizer sector - Sharma, Vijay Paul (International Food Policy Research Institute, 2014)
The contribution of chemical fertilizers towards increased agricultural production is well established. Indian agricultural policy focused on increasing productivity and modern inputs such as improved seeds (HYVs), irrigation, chemical fertilizers, etc. have played an important role in increasing crop production and productivity. Increased fertilizer use will continue to play an important role in increasing agricultural productivity given the diminishing land available for cultivation. Therefore, it is important to understand fertilizer use patterns and efficiency over time, the changing structure of fertilizer markets, the current policy environment and the role of various factors influencing fertilizer consumption. This brief is an attempt to address some of these issues